TARGETING PRC2 ENHANCES THE ANTITUMOR CYTOTOXIC CAPACITY OF ANTI-CD19 CAR-T CELLS AGAINST HEMATOLOGICAL MALIGNANCIES - MLR Carvalho; CO Andrade; MP Cabral-Piccin; GS Kinker; GAF Vitiello; L Abdo; RAG Cambui; MH Bonamino; TS Medina (Hematology, Transfusion and Cell Therapy)
Chimeric Antigen Receptor (CAR) T cell therapy was adopted as a clinical modality for patients with relapsed/refractory hematological malignancies. Despite the clinical efficacy of CAR-T cell therapy, a considerable fraction of patients still relapses during the first months following CAR-T cell infusion. The limited CAR-T cell efficiency is thought to relate to epigenetic mechanisms involved in T-cell suppression and dysfunction. Here, screening of multiple epigenetic inhibitors revealed that targeting PRC2 consistently enhanced the cytotoxic/effector phenotype of CD8 T-cells. Notably, PRC2 inhibition promoted the differentiation of GZMB+ effector memory 19BBζ CAR-T cells and enhanced their antitumor activity both in vitro and in vivo. Consistent with their long-lasting antitumor activity, PRC2-inhibited 19BBζ CAR-T cells did not exhibit any signs of dysfunctionality/exhaustion. Furthermore, TCR restimulation along with PRC2 inhibition of patient-derived anti-CD19 CAR-T cells also induced the development of GZMB+ effector memory cells and elicited potent antitumor responses against CD19+ Daudi cells. In line with this, thegene signature derived from in-house PRC2-inhibited 19BBζ CAR-T cells was enriched in tisagenlecleucel (tisa-cel) BBζCAR-T cell therapy responders with large B-cell lymphoma. Collectively, our results demonstrated that targeting PRC2 may be a promising approach to enhance a functional effector program in CAR-T cells against hematological malignancies.